EFL TEACHER’S ATTITUDES ON THE ASSESSMENT IN 2013 CURRICULUM: NARRATIVE INQUIRY STUDY - Fentri Effani; Muhammad Reza Pahlevi; Sumarta Sumarta (Universitas Muhammadiyah Tapanuli Selatan, 2021)
The purpose of this study is to identify EFL teacher’s attitudes based on the 2013 curriculum assessment in the Senior High School. It is aim to give illustration to the teachers on how to do on the 2013 curriculum. This research used qualitative analysis and narrative inquiry as a research design, The reason is narrative inquiry is related to the theme of this research, where this study wants to find out how attitudes are related to the practice of a teacher when assessing students, so this is closely related to narrative inquiry which focuses someone to tell experiences that have occurred. Semi-structured interviews will be conducted to obtain information about the EFL teacher’s attitudes about the assessment. The results of this study there are three important findings, namely: teacher’s emotional response to the assessment based on 2013 curriculum including teacher feels enjoy, accused, challenged and confused, the teacher carries out the aspects in authentic assessment well, and teacher uses alternative tools to carry out learning.